Student Engagement in Flipped English Classrooms: A Case Study of General English for Adults in an English Course in Jakarta - Fira, Chairunnisa Nurul; Permana, Sudarya; Mayuni, Ilza (STAIRS: English Language Education Journal, 2023)
This research investigates the influence of flipped learning on the engagement of adult participants in non-formal English language programs, considering diverse language proficiency levels. Employing a comprehensive methodology involving observations, interviews, and surveys, the study assesses engagement indicators and captures participants' perspectives. The incorporation of pre-class materials emerges as a significant contributor, empowering students to anticipate and prepare for in-person sessions, thereby fostering confidence and active participation in class discussions. The integration of collaborative group work further enhances engagement by introducing diverse viewpoints. Survey findings align with observations and interviews, affirming the effectiveness of the flipped learning model in augmenting student engagement. The approach also positively impacts students' perceptions of English learning, encouraging a deeper exploration of its practical relevance. This study highlights the crucial role of flipped learning in fostering dynamic and meaningful student engagement, offering valuable insights for educators seeking to optimize their teaching methodologies. Acknowledging limitations in sample size and educational context, the research emphasizes the necessity for future studies in more diverse settings.